EARLY LABORATORY DIAGNOSIS OF LUNG CANCER (Scientific Conference on Multidisciplinary Studies, 2025)
The objective of this study is to evaluate the effectiveness of modern clinical laboratory methods in the early diagnosis of lung cancer by analyzing cytological changes in sputum and pleural fluid, and to assess the sensitivity and specificity of these diagnostic tools.